Investigating the influence of the pressure distribution in a membrane module on the cascaded membrane system for post-combustion capture. (August 2015) - Brinkmann, Torsten; Pohlmann, Jan; Bram, Martin; Zhao, Li; Tota, Akos; Jordan Escalona, Natividad; de Graaff, Marijke; Stolten, Detlef
Abstract: Polyactive ® membranes show promising properties for CO2 separation from flue gas. An investigation of different module types using Polyactive ® membranes was carried out for this paper. A test rig was built to explore, amongst other process parameters, the pressure drop in envelope-type membrane modules. The experimental data and simulation results were compared with quite good consistency. This validation enabled further simulations for different modules in a virtual pilot plant configuration. Applying the data from the pilot plant simulation to a reference power plant, the scaled-up cascaded membrane system was analyzed using different membrane modules. Considering the required membrane area, energy consumption and pressure drop in different modules, a counter-current membrane module configuration exhibited the best performance and had a marginal advantage in comparison with the chemical absorption process.